ADAPTIVE GOVERNANCE DALAM MEWUJUDKAN PELAYANAN PRIMA DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PEKANBARU PADA TAHUN 2021-2022 - Meifabella, Tengku Syarifah; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Adaptive Governance is one of the government's efforts to adapt amid abnormal circumstances, in this case due to the co-19 pandemic. The government is required to adapt even though in a different way or method in order to continue to carry out government administration activities. Of course, administration of government related to public services must continue. This is where the government's task is to find ways to adapt for the continuity of the implementation of public services. The government's challenge is to find a way so that public services do not only operate out of necessity, but must create public services that are prime in 2021-2022 or what is called the transitional period, namely the Covid-19 pandemic towards the New Normal. The research method used is a qualitative method by explaining descriptively. The type of research data used is primary data in the form of data obtained from research informants and secondary data obtained from related documents that can support data for research. The research location is the Pekanbaru City Investment and One-Stop Service Office (DPMPTSP). This study found that the Pekanbaru City DPMPTSP was able to adapt in 2021-2022 as evidenced by the increase in the amount of licensing data caused by information technology innovations that simplify and cut the flow of Public Services such as the SIMOLEK, SIAP and SIMPEL applications. In addition, DPMPTSP also maintains the Community Satisfaction Index (IKM) in 2021 by achieving a B (good) grade. Other things can also be seen in the ability of the City of Pekanbaru DPMPTSP to empower human resources with training and upgrading to support the capacity of employees. Furthermore, adaptation can also be seen through system modifications, in this case the Pekanbaru City DPMPTSP routinely checks the network so that there are minimal errors when working. In addition, the Pekanbaru City DPMPTSP also routinely collaborates and coordinates both internally and externally. Of course, what cannot be separated from all the adaptations that have been made is the skill of the Head of the Pekanbaru City DPMPTSP Office in leading internally and in making decisions and policies for the common good. Keywords: Adaptive Governance, Excellent Service, Technology Innovation